2017
DOI: 10.4236/ym.2017.14023
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Nephropathy by Some Natural Sources of Antioxidants

Abstract: Nephrotoxicity is one of the most common kidney problems and occurs when the body is exposed to a drug or toxin. Natural sources of antioxidants may serve as a vital source of potentially useful new compounds for the development of an effective therapy to combat a variety of kidney problems. Natural antioxidants have a variety of biochemical actions such as inhibition of reactive oxygen species production, scavenging of free radicals. The present review aims to summarize the recent articles which studied some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 128 publications
1
23
0
Order By: Relevance
“…Natural antioxidants have a variety of biochemical actions such as inhibition of the production of ROS and scavenging of free radicals. 2,61,62 Azab et al, 2 reported that consumption of fenugreek, curcumin, peppermint, parsley, rosemary, garlic, pomegranate, sesame, and propolis were shown protective effects against renal diseases and nephrotoxic agents induced renal dysfunctions in experimental animals and human. The nephroprotective effect may be due to the inhibition of tissue lipid peroxidation and enhancement of antioxidant activity.…”
Section: Natural Antioxidantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural antioxidants have a variety of biochemical actions such as inhibition of the production of ROS and scavenging of free radicals. 2,61,62 Azab et al, 2 reported that consumption of fenugreek, curcumin, peppermint, parsley, rosemary, garlic, pomegranate, sesame, and propolis were shown protective effects against renal diseases and nephrotoxic agents induced renal dysfunctions in experimental animals and human. The nephroprotective effect may be due to the inhibition of tissue lipid peroxidation and enhancement of antioxidant activity.…”
Section: Natural Antioxidantsmentioning
confidence: 99%
“…An imbalance between free radicals and antioxidants leads to oxidative damage of proteins, fat, nucleic acids, and carbohydrates. 1,2 Antioxidants have protected the body from the harmful effect of the free radicals. 2,3 Endogenous antioxidants defense against the reactive oxygen species are strengthened by natural antioxidants that strengthen them and restore the optimal balance by neutralizing the ROS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to chemical reagents like ethylene glycol, CCl 4 , sodium oxalate, and heavy metals induce nephrotoxicity. Prompt recognition of the disease and termination of responsible drugs are usually the only necessary therapy (Azab et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, propolis is known to prevent cells from oxidative damage as an antioxidant. Many vegetables and fruits were studied in those aspects, among which propolis was superior [5,6,7] . One of these studies indicated that the antioxidant capability of propolis was 62 and 120 times of that of pomegranate and tomato, which were previously recognized as the most effective antioxidants [8] .…”
Section: Propolismentioning
confidence: 99%